Upaya Pengembangan Kecerdasan Sosial Anak Melalui Pembiasaan TOMAT (Tolong, Maaf, Terima Kasih) - Karunia, Anggie; Purbasari, Imaniar; Khamdun, Khamdun (PGSD Universitas Muria Kudus, 2024)
This research aims to (1) find out how the TOMAT (Help, Sorry, Thank You) habituation program is implemented and (2) find out what factors influence the implementation of habituation in the development of students' social intelligence in SD 2 Tenggeles.This type of research is descriptive qualitative with a narrative method or approach which was carried out at SD 2 Tenggeles, Mejobo District, Kudus Regency, taking class II teachers as subjects with a total of 18 students. Data was taken using interview and observation techniques. Interviews were conducted using interview instruments for students and teachers, while observations were carried out to observe the habituation of TOMAT (Please, Sorry, Thank You) in class 2 students at SD 2 Tenggeles. Analysis of research data qualitatively. Data on the implementation of the TOMAT program observed and recorded in interview activities are presented in narrative sentences and concluded according to field data.The results of the analysis show that the behavior of SD 2 Tenggeles students in implementing the TOMAT (Help, Sorry, Thank You) habituation program is actually able to help develop students' social intelligence as demonstrated by their behavior of helping each other, the ability to control themselves, having endurance when facing a problem, self-motivated, able to regulate mood, ability to empathize and build relationships with other people, interact with other people, have self-awareness, consistently say TOMAT (Help, Sorry, Thank You) in the school environment even though sometimes you still have to be reminded. There are factors that influence students' social development, including individual factors, environmental factors, family factors with different dominance. The differences in the dominance of these factors then give rise to differences in each child, or what is more often called individual differences